What psych verbs and other verbs disclose about the role of Semantic Prominence and Thematic Hierarchy in affixal selection - Rodrigues, Alexandra Soares (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2021)
This paper analyses the construction of deverbal adjectives in European Portuguese, focusing on the interface between morphology and semantics, specifically on the role of Thematic Hierarchy and Semantic Prominence on affixal selection. Supported by paradigmatic morphology, the paper shows that suffixes that work in macroparadigms of deverbal adjectives establish a relationship with specific semantic features of the lexical-semantic structure of the base verb in order to construct the derivative. The analysis concludes that suffixes are sensitive to thematic hierarchy, which is based on the semantic prominence of features of the verbs’ theta-roles at work in the paradigm. Data from psych verbs is highly relevant to this finding. The paper is dedicated to Professor Ana Maria Brito, who has always been keenly aware that scientific knowledge is not confined to a specific theory.